2010
DOI: 10.2337/dc10-0515
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroids Affect Triglyceride Handling, Glucose-Dependent Insulinotropic Polypeptide, and Insulin Sensitivity

Abstract: OBJECTIVETo evaluate metabolic effects of sex steroids in nonfasting and fasting conditions, independent from changes in body composition.RESEARCH DESIGN AND METHODSA randomized clinical trial was performed to create contrasting sex steroid levels in healthy young men: by letrozole (aromatase inhibitor) to lower estradiol (E2) and increase testosterone (group T, n = 10) versus letrozole plus E2 patches to lower T and raise E2 (group E, n = 10). Mixed meals and hyperinsulinemic-euglycemic clamps were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 15 publications
5
22
0
Order By: Relevance
“…Only two studies 7,20 in this aspect were available and their findings were consistent with ours even though they did not take SHBG into account. Another clinical trial revealed that short-term elevation of testosterone had positive effect on postprandial TG handing but not in the fasting TG levels, 24 which was also in line with our observations. The mechanism of these findings is not clear.…”
Section: Discussionsupporting
confidence: 91%
“…Only two studies 7,20 in this aspect were available and their findings were consistent with ours even though they did not take SHBG into account. Another clinical trial revealed that short-term elevation of testosterone had positive effect on postprandial TG handing but not in the fasting TG levels, 24 which was also in line with our observations. The mechanism of these findings is not clear.…”
Section: Discussionsupporting
confidence: 91%
“…On the one hand, E2 may display beneficial effects on endothelial cells, inhibiting migration, proliferation and collagen production in vascular smooth muscle cells, and E2 may improve the function of cardiac myocytes under ischaemic stress 28. On the other hand, E2 could induce inflammatory and pro-coagulant factors, 28 and appear to increase triacylglycerol levels 38. In fact, E2 may play a major role in cell death, although effects on cells of males and females could be different 39…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, data support the relationship of low testosterone to obesity and metabolic syndrome [37e40], a finding that may be explained by the increased activity of aromatase, an enzyme that converts testosterone to estradiol and it is located in the visceral fat [41]. Further, low levels of testosterone are related to insulin resistance [42,43]. The cross-talk between low testosterone, obesity, metabolic syndrome and insulin resistance may explain part of the high incidence of hypertension and diabetes [2,3,44] and the increased cardiovascular risk associated with low testosterone [8e12,44].…”
Section: Testosterone and Cardiovascular Riskmentioning
confidence: 92%